Exploring Mobile Learning and Technological Integration in Modern Classrooms - Kinjalben Chandulal Thakkar; Dr. Pavankumar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of mobile learning and technology in modern classrooms has transformed educational practices, fostering engagement and improving learning outcomes. This study examines the correlation between mobile learning tools, resource availability, and student engagement through a survey of 630 students from government and private schools. Findings highlight the significant potential of mobile learning in enhancing comprehension and participation, while also identifying challenges related to resource disparities, teacher preparedness, and infrastructure limitations. The study underscores the need for equitable resource distribution, continuous teacher training, and tailored policy interventions to bridge digital divides and optimize technology’s impact on education.